Penerapan Strategi Think Aloud Untuk Meningkatkan Keterampilan Membaca Teks Naratif Kelas X-9 MAN 1 Kab. Pasuruan - Ariadi, Eka Sugeng (Inovasi: Jurnal Diklat Keagamaan, 2023)
Until now, the reading culture in Indonesia is still among the lowest in the world. This has an impact on the low ability or reading skills of students. One of the solutions provided by the government to overcome this problem is to issue a unique GLS Manual Series related to the Think Aloud Strategy for high school level and equivalent. The research, which was conducted using the Classroom Action Research (PTK) approach, aims to apply the think-aloud strategy to class X-9 at MAN 1 Pasuruan in the even semester of the 2022-2023 school year. The formulation of the problems in this study include: (1) how is the think-aloud strategy practiced in improving narrative text reading skills in class X-9 MAN 1 Pasuruan? and (2) to what extent can think aloud strategy improve narrative text reading skills in class X-9 MAN 1 Pasuruan? Based on the results of the implementation of cycle 1 and cycle 2, the researcher concluded, first, the implementation of the think-aloud strategy in class X-9 MAN 1 Pasuruan can be fully (100%) practiced in accordance with the references or guidelines that have been outlined in the literature review. Second, the application of the think-aloud strategy can significantly improve the reading skills of class X-9 students of MAN 1 Pasuruan both in the knowledge (cognitive) and skills (psychomotor) aspects. In the cognitive element, there was a very significant increase from cycle 1 to cycle 2. The same thing happened in the psychomotor element, although not too significant. Thus the second and third indicators of success where the mean score of class X-9 on the cognitive and psychomotor aspects of > 80% is well fulfilled. There are several suggestions for further research, first, the think-aloud strategy is very feasible to practice in the teaching and learning process in English subjects (mapel) and also other subjects because this strategy is able to improve the quality of students' thinking in understanding the text being read. Second, modeling a new strategy is also very much needed as an initial guide or guide for students to make it easier to practice independently when reading other texts. Finally, further research is needed in other subjects, besides English, by using the think-aloud strategy or modifying it with other strategies.